Strategi Pembelajaran dan Konsep Diri Terhadap Keterampilan Passing Bawah Bola Voli - - Saifu (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: This field experiment used factorial design in the sixth grade 9 state elementary school Kendari city. The 60 students was sampled from population with purposive random sampling technique. The collected data was analysed by two ways anova and Tuckey test. It can be concluded that there were no interaction between instructional strategy and self concept in teaching volly ball down passing.